Village Tapestry The History of Blowing Rock - Buxton, Barry M. (Appalachian State University, 1989)
Born in the Wallingford Clinic in 1949, Barry Buxton called the town of Blowing Rock home during his childhood. The youngest of seven children, he grew up in the mountains attending Blowing Rock elementary school and looked towards the nearby college, Appalachian State University, for his undergraduate studies. Graduate school took Dr. Buxton to the midwest, however he returned to Blowing Rock in the 1980s to assume a position at the Appalachian Consortium Press. It was during this time he was approached by Judith Burns to write a complete history of Blowing Rock. Published in 1989, A Village Tapestry is the result of a three year intensive study completed by Dr. Buxton. This book is the history of a small town in the mountains; however, for Dr. Buxton it is also an extension of his story in the village in which he was born.